Dopady (ne)konvenčních měnových politik vybraných centrálních bank na HDP a inflaci - Černohorská, Liběna; Klejzar, Vladimír (Univerzita Pardubice, 2018)
The aim of this paper is to analyze the influence of monetary policy on economic indicators – if monetary aggregate M3 has influence on consumer price index (CPI) and gross domestic product (GDP) in the Czech Republic, the USA, the Eurozone and Switzerland. Cointegration this selected indicator M3 is demonstrated in relation to the development of CPI and GDP using the Engle - Granger cointegration test. Data from the years 2007–2016 are included in the analysis. We determine the optimum delay using inforamtion criterion for all-time series analyzed. Then we analyzed the presence of a unit root using the Dickey - Fuller test and we excluded time series which appear to be stationary. If the conditions are met, testing then continued with the Engle - Granger test to detect cointegration relations, which would determine a relationship between selected indicators. Based on Engle-Granger test, we found that doesn´t exist cointegration relationship between M3 and CPI and GDP in the Czech Republic and the Eurozene ((un)conventional monetary policies are ineffective). On the contrary, in the case of the USA and Switzerland, the impact of the M3 monetary aggregate on GDP and CPI was confirmed ((un)conventional monetary policies are effective).
Keywords: central bank; cointegration test; unconventional monetary policy; M3; E51; E47; C32